Você está pedindo ou perguntando? Uma análise entonacional de pedidos e perguntas no português do Brasil (Revista de Estudos da Linguagem, 2007)
In this paper the intonation contours of yes/no questions and requestsin Brazilian Portuguese are compared. Speech synthesis was used toevaluate the relevance of the F0 configuration of nuclear andprenuclear pitch accents in the distinction between these twointonational patterns. Thirty-one resynthesized melodic versions ofthe sentence “Na festa destranca?” (At the party do you unlock it?/At the party would you please unlock it?) – which is ambiguous inPortuguese in its interpretation as a question or as a request – havebeen created. These versions, placed in four auditory tests, havebeen judged by twenty listeners who evaluated the effects of themodifications in the original sentence, in favor of its interpretationeither as a question or as a request. The results of the perceptiontests show that the opposition between the two melodic contours isdue to the direction of the F0 curve in the nuclear pitch accent,rising in the yes/no question and falling in the request. A phonologicalrepresentation of these patterns, based on distinct temporal alignmentsof the F0 peak in the final stressed syllables, is proposed.